The Effect of Ethanolic Extract of Bangle Rhizome (Zingiber purpureum Roxb.) on Reducing Blood Sugar Levels in Hyperglycemic Mice: In vivo and In silico Studies - Valerie Gerail Sitompul; Nugrahaningsih W. H (Journal of Science and Technology Research for Pharmacy, 2025)
Diabetes mellitus (DM) is a metabolic disease in which blood sugar levels are uncontrolled. Type 2 diabetes mellitus is uncontrolled blood sugar levels that occur due to insulin resistance or reduced body sensitivity to insulin. Treatment of type 2 diabetes mellitus, pharmacologically, uses oral antihyperglycemic drugs and injectable antihyperglycemic drugs. Although effective, antidiabetic drugs often cause adverse side effects. Indonesian people are concerned about synthetic drugs because of the potential side effects caused so that people are encouraged to look for more natural or herbal alternative treatments that are believed to have antidiabetic activity, one of which is ginger. Bangle (Zingiber purpureum Roxb.) is one of the plants that belongs to the zingiberaceae or ginger family. Bangle rhizome has a major compound of curcumin of 2,633% w/w and phenylbutanoid which has antioxidant, anti-inflammatory, and AMPK (AMP-activated protein kinase) agonist activity. With this activity, the antidiabetic potential of bangle rhizome was tested in vivo using alloxan-induced hyperglycemic mice, observed in 14 days with bangle rhizome extract doses of 100mg/kgBW, 200mg/kgBW, 400mg/kgBW, and in silico to determine compounds that have antidiabetic activity. The results obtained from the in vivo test for reducing blood sugar on days 7 and 14 had a significance value of 0.383 (p>0.05) and 0.253 (p>0.05) which means that the administration of bangle rhizome extract did not have a significant effect on reducing blood sugar in hyperglycemic male mice. The in silico test conducted was in line with the in vivo results where bangle rhizome extract had greater potential for anticancer, anti-inflammatory, and fat metabolism activities. The PASS Online results did not show any activity related to insulin sensitivity or alpha glucosidase inhibitor activity.